Effects of compound treatment of exogenous feed enzymes and microwave irradiation on in vitro ruminal fermentation and intestinal digestion of guar meal - NARIMANI, S; TAGHIZADEH, A; SIS, N MAHERI; PARNIAN, F; NOBARI, B BAGHBANZADEH (The Indian Journal of Animal Sciences, 2014)
Effects of compound treatments of microwave irradiation (900 W) for 0, 2 and 4 min and exogenous feed enzymes at the application rate of 0, 250 and 500 g/ton on fermentation kinetics and digestibility of guar meal were evaluated by in vitro gas production and 3-step in vitro digestion techniques. Cumulative gas production was recorded at 2, 4, 6, 8, 12, 16, 24, 36, 48, 72 and 96 h of incubation and its kinetic was estimated using model: GP = A[1 - e-(t-L)]. To investigate ruminal and post ruminal digestion, the in situ and Ankom daisy-II incubation techniques were performed. Although enzyme supplementation levels had no significant effects on gas production, quadratic response to enzyme levels was observed after 12 h post-incubation and continued up to 96 h post-incubation. Microwave irradiation did not show significant impact on cumulative gas production. Interaction of enzyme and microwave irradiation was also not significant. While, there was no significant difference in potential gas production parameter (A) due to the effects of exogenous enzyme levels, microwave irradiation times or their interactions, gas production rate (c) was higher than control for all enzyme treatments. Significant effect of feed enzyme and microwave irradiation interaction was observed on guar dry matter (DM) digestibility. Post-ruminal digestibility of CP in compound treatment of no enzyme and 2 min microwave irradiation has the lowest digestibility (905.4 g/ kg). Moreover, interaction between enzyme and microwave irradiation on guar meal post-ruminal CP digestibility was significant. It was concluded that heat processing of high protein oil seed meals followed by exogenous feed enzyme supplementation might lessen the possible Maillard reaction effects of heat processing. In conclusion, according to present study such order of compound treatments might shift protein digestion from rumen to post- ruminal sites. Consequently, this will improve protein and amino acids profile of followed digesta to small intestine, which is crucial in animal productivity performance.